2013
DOI: 10.1088/0964-1726/22/8/084012
|View full text |Cite
|
Sign up to set email alerts
|

A nonlinear auxetic structural vibration damper with metal rubber particles

Abstract: The work describes the mechanical performance of a metal rubber particles (MRP) damper design based on an auxetic (negative Poisson's ratio) cellular configuration. The auxetic damper configuration is constituted by an anti-tetrachiral honeycomb, where the cylinders are filled with the MRP material. The MRP samples have been subjected to quasi-static loading to measure the stiffness and loss factor from the static hysteresis curve. A parametric experimental analysis has been carried out to investigate the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
72
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(72 citation statements)
references
References 32 publications
0
72
0
Order By: Relevance
“…Auxetic materials have been initially observed in ferromagnetic films [1], face centered cubic crystals [2], hard cyclic hexamers [3,4], and foams [5][6][7][8]. Due to their counter-intuitive properties, auxetic materials have been investigated as smart materials for potential applications including cushion materials [9], stents [10,11], pressure vessels [12], sensors [13], morphing airfoils [14,15], smart folding structures [16], smart metamaterials [17], aeroengine fan blades [18], and vibration dampers [19], to name a few. Arising from their unique properties, the mechanical performance of auxetic solids has been investigated [20][21][22][23][24][25][26][27][28][29][30][31][32][33], including their elastic stabilities [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Auxetic materials have been initially observed in ferromagnetic films [1], face centered cubic crystals [2], hard cyclic hexamers [3,4], and foams [5][6][7][8]. Due to their counter-intuitive properties, auxetic materials have been investigated as smart materials for potential applications including cushion materials [9], stents [10,11], pressure vessels [12], sensors [13], morphing airfoils [14,15], smart folding structures [16], smart metamaterials [17], aeroengine fan blades [18], and vibration dampers [19], to name a few. Arising from their unique properties, the mechanical performance of auxetic solids has been investigated [20][21][22][23][24][25][26][27][28][29][30][31][32][33], including their elastic stabilities [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the 1 -order equation (31) is linear in the unknown λ , the 2 -order equation (32) is linear in the unknown λ and so on. Therefore, the cascade solution (null if the numerator vanishes) for the lowest order eigensensitivities is…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Among the available chiral topologies, the class of antitetrachiral materials is attracting major attention for its strong auxeticity, accompanied by a marked anisotropy of the elastodynamic response [12,[28][29][30][31][32]. Nonetheless, the microstructural complexity of the anti-tetrachiral periodic cell may act as a partial barrier against fully-analytical formulations.…”
Section: Introductionmentioning
confidence: 99%
“…Budarpuet al proposed a chiral‐core morphing airfoil with elliptical nodes, and the geometrical configuration of the chiral‐core structure can be optimized to meet various morphing behaviors and global stiffness requirements, thus improving the aerodynamic performance of the airfoil. Ma et al proposed the design of anti‐tetrachiral vibration damper sandwich composite structures, where the cylinders are filled with the metal rubber particles (MRP) material. Static and dynamic vibration tests are performed to assess the performances of the integrated auxetic‐MRP damper structures; it is found that the lightweight integrated auxetic damping panel exhibit higher damping and loading capability.…”
Section: Introductionmentioning
confidence: 99%